STORYTELLING TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL (KETERAMPILAN SOSIAL DAN MASALAH PERILAKU) ANAK USIA 5-6 TAHUN - Andani, Stefani; Santi, Eka; Lestari, Dhian Ririn (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Child development at the age of 5-6 years can occur biologically, psychologically andsociologically. The emotional social development (social skill and problem behavior) of 5-6 yearsolds can be improved by storytelling. The aim of this study to know the influence of storytelling onemotional social development (social skill and problem behavior) of children 5-6 years old inPAUD Panenga Palangka Raya. This research used pre-experimental design with one grouppretest posttest design. The respondents amount 14 people taken in total sampling withinstruments are Preschool and Kindergarten Behavior Scales (PKBS) and storytellinginstruments. Data analysis used Wilcoxon Test with p value 0,002 for social skill and p value0,007 for problem behavior it is mean (p <0,05), so there is influence storytelling to emotionalsocial development of 5-6 years old child in PAUD Panenga Palangka Raya. Storytelling wasvery useful for nursing staff to optimize the emotional social development (social skill andproblem behavior) of children 5-6 years old.